Translation, cross-cultural adaptation and psychometric evaluation of the Serbian Ankylosing Spondylitis Quality of Life (ASQoL) Questionnaire (refers to r-axSpA) and its relations with disease activity and functional status indices - Mirjana Zlatkovic-Svenda; Ana Djokic; Andjela Perunicic; Marija Zdravkovic; Slavica Pavlov Dolijanovic; Jeanette Thorpe; Dejan Dudok; Jelena Milicevic; Dejana Petrovic; Goran Radunovic (Journal of Patient-Reported Outcomes)
Abstract Objectives To translate, cross-culturally adapt and validate the Serbian Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire, e.g. according to the new nomenclature Radiographic-Axial Spondyloarthritis (r-axSpA), and to relate it to disease activity and functional status domains. Methods Four stages were accomplished: (1) Bilingual and lay panel for translation and cross-cultural adaptation (2) Cognitive debriefing interviews (assessing the language and cultural equivalence of the concepts used in the Serbian ASQoL translation) for face and content validity (3) Psychometric evaluation: (a) convergent validity by NHP as a comparator scale and (b) known group validity by correlations with disease activity and overall health status and reliability (internal consistency and test-retest reliability) (4) Independent regression analyses for relations between ASQoL and ASDAS, BASDAI, BASFI, Schober’s test, respiratory index and SPARCC were used. The statistical program SPSS (version 21; IBM, Armonk, NY, USA) was used. Results The bilingual panel made a unified version of the translated documents, a lay panel confirmed the clarity of the questionnaire. Cognitive debriefing interviews with 10 patients evaluated the Serbian ASQoL as clear, precise, easy to complete. The psychometric properties with 60 randomly selected patients showed good convergent validity between ASQoL and NHP domains of pain (r = 0.79), emotional reactions (r = 0.78), physical activity (r = 0.77) and energy (r = 0.75). The internal reliability was 0.95 and 0.91 (1st and 2nd administration), respectively, and the test-retest reliability was 0.84. Regression analyses showed highly significant relationships (p < 0.001) between ASQoL and ASDAS (R²=0.403), BASDAI (R²=0.564) and BASFI (R²=0.444). Conclusion The Serbian ASQoL demonstrated good psychometric properties and significant relationships with disease activity and functional status and is recommended for quality of life assessment in Serbian-speaking ankylosing spondylitis (radiographic axial spondyloarthritis) patients, both in clinical practice and clinical research.